PENGETAHUAN MASYARAKAT TERHADAP KEBIJAKAN PEMERINTAHDALAM PENANGANAN BECANA KEBAKARAN HUTAN DAN LAHAN DI SEKITAR TAMAN NASIONAL TESSO NILO - Nurdianto, Kristian; Oktorini, Yossi; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
National Park is a nature conservation area, in management there are many threats that can damage or reduce the national park area. One such threat is forest fires and land. Forest fires in Tesso Nilo National Parks (TNTN) generally caused by land clearing. Mechanisms for resolving problems of forest and land fires that occurred in TNTN at comprehensive, one application of the policy. Given the function of the National Park as a life support system protection, preservation of biological diversity, sustainable use of natural resources and ecosystems. The purpose of this study was to determine people's knowledge of government policy in the management of land and forest fire disasters. Methods of data collection by way of documentation, interviews and questionnaires. Sampling using purposive sampling method and quoted sampling Number of samples this study of 38 people with the details, two (2) persons Hall TNTN, 4 (four) NGO, 2 (two) Forest Service Pelalawan, and 30 community living TNTN around. The data obtained, processed using techniques percentage and compiled into the form of tables, so it can be deduced. The results showed Lubuk Kembang Bunga Village, Air Hitam Village and Bagan Limau Village generally do not know about the existence of government policy in the handling of forest fires and land applied in TNTN. Keywords : Policy, forest fires, National Park